The Influence of Social Media on Public Relations as a Reinforcement of Higher Education Reputation - Ahmad Fauzi; M. Aqil Fahmi Sanjani; Abdul Wahid Zaini; Musammil Lateh (Managere: Indonesian Journal of Educational Management, 2025)
This study aims to analyze the role of social media in public relations management in Islamic higher education institutions with a focus on ethical governance and use, strategic platform utilization, and its impact on institutional reputation. As digital communication becomes increasingly important in higher education, universities must adapt to this trend by implementing strategies that align with institutional values ​​and effectively meet the needs of their stakeholders. This study explores social media management practices using a qualitative approach and a case study method. Data was collected through interviews with students, lecturers, and staff, as well as analysis of documentation of social media platforms used by the university. The results show that ethical governance and the use of social media have strengthened institutional communication by aligning published content with Islamic values ​​and ethics. Strategically, the institution has utilized various platforms, including Instagram, Facebook, Twitter, and YouTube, to target specific audiences and increase engagement. The impact on reputation is evident in the increase in public interaction and positive perceptions despite the potential risks arising from irrelevant or untimely content. This study is expected to contribute to understanding effective social media governance in higher education institutions, emphasizing the importance of ethical practices, strategic content delivery, and reputation management.